User acceptance of DeSkab mobile application for early detection of scabies in Indonesia - Widaty, Sandra; Friska, Dewi; Bramono, Kusmarinah; Sari, Siti Maulidya; Darmawan, Irene; Kekalih, Aria (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: Individual case management strategy is not suitable for reducing scabies transmission, especially in high prevalence settings. A community-based approach has been proposed to control scabies. We developed a mobile application, called DeSkab, to empower non-medical personnel in crowded populations e.g., boarding schools, and to aid the identification of skin lesions suggesting scabies based on the cardinal signs of scabies. Early treatment and prevention of scabies transmission is expected to follow this approach. This was the initial development of the DeSkab mobile application which aims to assess user acceptance. Methods: The DeSkab mobile application was designed using Java and XML, supported by Google's Android. The scabies detection and education features were the app’s key distinctive aspects. An online survey was performed, aimed at potential users, including boarding school teachers and healthcare workers. The survey was divided into four sections: application design and user-friendliness, early detection data entry and interpretation, education features, and user recommendations. Result: Overall, users' acceptance of this application was good. More than 70% of the users gave good feedback for the application. Using mobile health makes it easier for the users to find information about scabies and check whether their skin lesions are suggestive of scabies. Conclusion: This application is expected to help expand scabies detection, especially in crowded communities. Improvements must be made to the interface, data entry, and educational material for the app's next iteration. Further study is needed to determine how mobile health application can improve scabies detection in communities.